2000
DOI: 10.1038/75057
|View full text |Cite
|
Sign up to set email alerts
|

High susceptibility to bacterial infection, but no liver dysfunction, in mice compromised for hepatocyte NF-κB activation

Abstract: Based on the essential involvement of NF-kappaB in immune and inflammatory responses and its apoptosis-rescue function in normal and malignant cells, inhibitors of this transcription factor are potential therapeutics for the treatment of a wide range of diseases, from bronchial asthma to cancer. Yet, given the essential function of NF-kappaB in the embryonic liver, it is important to determine its necessity in the liver beyond embryogenesis. NF-kappaB is normally retained in the cytoplasm by its inhibitor Ikap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(115 citation statements)
references
References 22 publications
5
109
1
Order By: Relevance
“…14,32 Similarly, 2 independent laboratories confirmed that mice with hepatocyte-targeted deletion of ikk␤ (ikk␤ hep ) develop with normal liver structure and function and do not display elevated susceptibility to hepatocyte apoptosis induced by soluble TNF-␣ or lipopolysaccharide. 33,34 It is concluded that the canonical IKK␤ driven NF-B pathway is not essential for hepatocyte survival in the normal liver or upon challenge from physiological doses of endotoxin or TNF-␣.…”
Section: Nf-b As a Tumor Suppressor In Hepatocytesmentioning
confidence: 90%
See 1 more Smart Citation
“…14,32 Similarly, 2 independent laboratories confirmed that mice with hepatocyte-targeted deletion of ikk␤ (ikk␤ hep ) develop with normal liver structure and function and do not display elevated susceptibility to hepatocyte apoptosis induced by soluble TNF-␣ or lipopolysaccharide. 33,34 It is concluded that the canonical IKK␤ driven NF-B pathway is not essential for hepatocyte survival in the normal liver or upon challenge from physiological doses of endotoxin or TNF-␣.…”
Section: Nf-b As a Tumor Suppressor In Hepatocytesmentioning
confidence: 90%
“…For example, both ⌬N-I B␣ and ikk␤ hep livers were more susceptible to concanavalin-A-induced hepatocyte apoptosis. 32,33 This may reflect the ability of concanavalin-A to trigger activation of both TNFR1 (the receptor for soluble TNF-␣) and TNFR2 (the receptor for membrane bound TNF-␣), which results in robust and prolonged activation of proapoptotic Jun N-terminal kinase. 33 Because concanavalin-A provides a model for T cell-mediated hepatocyte death, it is possible that IKK␤-driven activation of NF-B functions as an important hepatocyte survival signal in alcoholic and viral liver disease.…”
Section: Nf-b As a Tumor Suppressor In Hepatocytesmentioning
confidence: 99%
“…Transgenic expression of degradation-resistant IkBa and IkBb isoforms Degradation-resistant IkBa and IkBb mutants (IkBm) that function as dominant inhibitors of NF-kB activation when expressed under the control of tissue-specific or developmentally restricted promoters have been used to probe NF-kB function in a range of cell types in mice, including B (Bendall et al, 1999) and T lymphocytes (Boothby et al, 1997;Esslinger et al, 1997;Attar et al, 1998;Ferreira et al, 1999;Hettmann et al, 1999;Voll et al, 2000;Hettmann and Leiden, 2000), muscle (Cai et al, 2004), neurons (Fridmacher et al, 2003), hepatocytes (Lavon et al, 2000;Cai et al, 2005), heart (Dawn et al, 2001), pancreas (Norlin et al, 2005) and skin (Seitz et al, 1998;van Hogerlinden et al, 1999). Although this approach has been highly successful, IkBm expression targeted to a particular tissue has been documented to generate distinct phenotypes, or a phenotype of varying severity in different transgenic founder lines.…”
Section: Ijb Proteinsmentioning
confidence: 99%
“…The ToI-␤ mouse model was generated by cross-breeding two transgenic lines of mice: one carrying the inversely positioned ⌬NI B␣ (with the N-terminal deleted) and luciferase genes (⌬NI B␣-Luc), regulated by a bidirectional tetracycline-responsive element against a C57B͞6 ϫ BALB͞c background (44) and the second expressing the reverse tetracycline transactivator (rtTA) under the control of the rat insulin II promoter, consisting of the 9.5-kb 5Ј flanking region of the gene (RIP7-rtTA) against the C3H ϫ BALB͞c background (45). Transmission of both transgenes was monitored by PCR analysis from tail DNA by using the appropriate primers.…”
Section: Methodsmentioning
confidence: 99%